2011
DOI: 10.1007/s11125-011-9207-5
|View full text |Cite
|
Sign up to set email alerts
|

Effective inclusive education: Equipping education professionals with necessary skills and knowledge

Abstract: As a result of educational reforms, students with disabilities are educated in inclusive settings to a greater degree than ever before. Regrettably, many teachers report that they feel unprepared to work effectively with these students. Because teacher effectiveness is strongly linked to student outcomes, these perceptions of inadequacy are clearly problematic. Improved teacher preparation is a necessity. Yet, teacher educators face their own challenges when trying to keep up with current literature and a rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 19 publications
3
37
0
4
Order By: Relevance
“…Student outcome strongly depend on the effectiveness of the teaching, but regrettably many teachers report that they feel unprepared to work effectively with students with special needs (Smith, 2011). In addition, there are some studies which found that the most of teachers who work in a different field than their own, do not have sufficient field knowledge and this affect their teaching adversely (Turkish Educational Association, 2009;Nizamoğlu, 2006;Scout, 2005;Kumar, 2003;Oral, 2000).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Student outcome strongly depend on the effectiveness of the teaching, but regrettably many teachers report that they feel unprepared to work effectively with students with special needs (Smith, 2011). In addition, there are some studies which found that the most of teachers who work in a different field than their own, do not have sufficient field knowledge and this affect their teaching adversely (Turkish Educational Association, 2009;Nizamoğlu, 2006;Scout, 2005;Kumar, 2003;Oral, 2000).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Researchers, though, continue to argue that training for preparing teachers to become inclusive practitioners lags far behind policy (Armstrong, Armstrong, & Spandagou, 2010;Lancaster & Bain, 2007), and that newly graduated teachers still suggest that they are ill prepared to work in inclusive schools (Winter, 2006). Perceptions of inadequacy in teacher preparation are challenging, as without the essential skills and strategies to become inclusive practitioners, teachers are unable to successfully meet the needs of their learners (Smith & Tyler, 2011). Further, while training teachers in the skills and practices needed for inclusion is invaluable, it is crucial that they are also accepting of the philosophy and supportive of an inclusive approach (Jordan, Schwartz, & McGhie-inclusion is more important than skill development (Cook, 2002) and that for inclusion to be successful it must be firmly grounded by support for the ideology (Forlin, 2012;Ross-Hill, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This research yielded important information pertaining to what middle school general education teachers, based on their preparation, training, and support, were able to do while facing high standards of accountability from outside agencies and school administration (Darling-Hammond;McLeskey & Billingsley, 2008;Smith & Tyler, 2011).…”
Section: Discussionmentioning
confidence: 99%